Developing and implementing a faculty development curriculum for Japanese family medicine residency faculty - Kenya Ie; Masato Narushima; Michiko Goto; Joel Merenstein; Stephen Wilson; Yousuke Takemura (Journal of General and Family Medicine, 2020)
Abstract Background Despite the increase in family medicine residency in Japan, there are only a few structured faculty development (FD) programs. The objective of this project was to construct a consensus on core competencies of faculty to develop a faculty development curriculum in a Japanese family medicine context. Methods In 2015, a private FD initiative in the Mie University initiated a curriculum development in collaboration with FD fellowship at the University of Pittsburgh. A literature review and subsequent Delphi process were conducted for core competency development. Based on the core competency list, we designed and implemented a 2‐year part‐time FD curriculum from 2016. A course evaluation using pre‐post confidence level was held during March 2017. Results Twenty‐eight objectives were defined in five core domains: 1) care management/family medicine principle, 2) leadership/professional development, 3) administrative/management, 4) teaching, and 5) research/scholarly activity. A pre‐post survey at the end of an academic year revealed a significant increase in learner confidence for “care management/family medicine principle” (P = .03), “teaching” (P < .01), and “research/scholarly activity” (P < .01), as well as the total score (P = .03). Conclusions A family medicine FD curriculum based on a faculty core competency list was developed by consensus in a Japanese family medicine context. The core competency was strongly context‐oriented, and the relevance of the FD topics and opportunities to apply to the participants' current positions may be inevitable for learner engagement. Further curriculum refinements will be required to see whether the curriculum could be used for faculty development in other family medicine residencies.